Investigations on weld joining of sisal CSM‐thermoplastic composites. Issue 2 (18th February 2014) - Hashmi, S.A.R.; Rajput, Rajendra Singh; Naik, Ajay; Chand, Navin; Singh, R.K.
<x xml:space="preserve">Abstract</x> An experimental study was conducted to investigate joint efficiency of both, butt, and lap joints of sisal CSM reinforced polymer composites. The thermoplastics, HDPE, and polypropylene (PP) were used separately as matrices in composites. Sisal‐HDPE composites exhibited excellent improvement in tensile strength that reached up to 47.5 MPa at 30 phr loading of sisal CSM as compared with 17.7 MPa of HDPE. Significant improvement in HDT was also observed that increased from 60.2 to 75°C on 0 to 30 phr reinforcement of sisal CSM in HDPE. Similar improvement was noticed with PP where in HDT improved from 69 to 87.6°C on incorporation of 0 to 30 phr sisal CSM. Hot tool welding process was employed for joining the composite materials. The joint efficiency of butt joint of HDPE was observed as 30%. It varied from 48 to 59% for lap joints of different sizes. The joint efficiencies of 20 mm lap joints of different compositions were observed as 59, 98, 75, and 58% in 0, 10, 20, and 30 phr Sisal CSM‐HDPE composites, respectively. Welded joint strengthening is attributed to partial reinforcement of interface that occurs during softening of matrix material which allowed spring back of originally pressed fibers followed by their repositioning in the welded part. POLYM. COMPOS., 36:214–220, 2015. © 2014 Society of Plastics Engineers